Imino Diels-Alder Reactions: Efficient Synthesis of Pyrano and Furanoquinolines Catalyzed by Antimony (III) Sulfate - Goudar, Mahesh A.; Jayadevappa, Honnali; Sudhakara, Aralihalli; Mahadevan, Kittappa M. (Letters in Organic Chemistry, 2008)
The Imino Diels-Alder reaction of N-benzylideneanilines with 3, 4-dihydro-2H-pyran and 2, 3-dihydrofuran proceeds smoothly to afford pyrano and furanoquinolines 3a-i and 4a-i in the presence of Antimony (III) Sulfate as catalyst. A concise and efficient synthetic route has been developed for one pot synthesis of pyrano and furano quinolines 6a-l and 7a-l by the reaction between anilines and 3, 4-dihydro-2H- pyran and 2, 3-dihydrofuran respectively in fairly good yields. This catalyst is inexpensive, easily available and it was also found that catalyst could be recovered quantitatively and reused without much loss of catalytic activity.
Keywords: aryl amines